Suppression of Toll‐Like Receptor 4 Dimerization by 1‐[5‐Methoxy‐2‐(2‐nitrovinyl)phenyl]pyrrolidine. Issue 10 (12th August 2016) - Ahn, Sang‐Il; Kim, Ji‐Soo; Gu, Gyo‐Jeong; Shin, Hyeon‐Myeong; Kim, Ah‐Yeon; Shim, Hyun‐Jin; Kim, Yeon Joo; Koh, Kwang Oh; Mang, Joo Yang; Kim, Dae Young; Youn, Hyung‐Sun
Abstract : Toll‐like receptor 4 (TLR4) recognizes lipopolysaccharide (LPS) and triggers the activation of myeloid differention factor 88 (MyD88) and the Toll/interleukin‐1 receptor domain‐containing adapter, inducing interferon‐β (TRIF)‐dependent major downstream signaling pathways. To evaluate the therapeutic potential of 1‐[5‐methoxy‐2‐(2‐nitrovinyl)phenyl]pyrrolidine (MNP), previously synthesized in our laboratory, its effect on signal transduction via the TLR signaling pathways was examined. Here, we investigated whether MNP modulates the TLR4 signaling pathways and which anti‐inflammatory target in TLR4 signaling is regulated by MNP. MNP inhibited the activation of nuclear factor‐κB (NF‐κB) induced by LPS (TLR4 agonist), and it also inhibited the expression of cyclooxygenase‐2 and inducible nitric oxide synthase. MNP inhibited LPS‐induced NF‐κB activation by targeting TLR4 dimerization in addition to IKKβ. These results suggest that MNP can modulate the TLR4 signaling pathway at the receptor level to decrease inflammatory gene expression. Abstract : The effect of 1‐[5‐methoxy‐2‐(2‐nitrovinyl)phenyl]pyrrolidine (MNP) on signal transduction via Toll‐like receptor (TLR) signaling was examined to evaluate its therapeutic potential. MNP inhibited the TLR4‐mediated activation of nuclear factor‐κB by lipopolysaccharide as well as the expression of cyclooxygenase‐2 and inducible nitric oxide synthase.